PENGARUH GOOD CORPORATE GOVERNANCE, FREE CASH FLOW DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN LQ45 DI BEI - Rizky Syamsudin; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this research to determine the influence of Good Corporate Governance, Free Cash Flow and Leverage towards Financial Performance of the LQ45 company. The data used in this study is secondary data. The population used is LQ45 company at BEI for the period 2015-2017. The sampling technique was done by purposive sampling method. The sample of this research is 38 companies. Data analysis was done by using multiple linier regression method. The result of this study indicate that Simultaneously, board of commissioner, independent commissioner, board of director, audit committee, managerial ownership, institutional ownership, free cash flow and leverage significantly affected the Financial performance. Partially, board of commissioner, independent commissioner, board of director, institutional ownership, and leverage didn’t significantly affect the Financial performance. Audit committee negatively and significantly affect the Financial performance. Meanwhile, managerial ownership and free cash flow positively and significantly affect the Financial performance. Keywords : Good Corporate Governance, Board of Commissioner, Independent Commissioner, Board of Director, Audit Committee, Managerial Ownership, Institutional Ownership, Free Cash Flow, Leverage, Financial Performance